Depression symptoms and mortality in elderly peruvian navy veterans: a retrospective cohort study - Astorga-Aliaga, A. (2022)
Abstract: Our study was design to determine the association between depressive symptoms and mortality in adults over 60 years old Navy Peruvian Veterans. We performed a retrospective cohort study based on a previous cohort study. A total of 1681 patients over 60 years old were included between 2010–2015. Demographic information, self-reported information about falls, physical frailty assessment, tobacco consumption, hypertension, Type 2 Diabetes Mellitus, Chronic Obstructive Pulmonary Disease and was collected. Depression was assessed by the short form of the Geriatric Depression Scale. We found that depressive symptoms were present in 24.9% of the participants and 40.5% of them died. Mortality risk in patients with depressive symptoms, physical frailty, and male sex was: RR of 23.1 (95% CI: 11.7–45.7), 3.84 (95% CI: 2.16–6.82), and 1.37 (95% CI: 1.07–1.75) respectively. We concluded that depressive symptoms in Peruvian retired military personnel and their immediate relatives are high and are significatively associated with mortality. Also, being male and frail was associated with an increased risk of death. This reinforces that early detection and assessment of depressive symptoms could be an opportunity to improve the health status of older adults.